IMPLEMENTASI PENERAPAN COSO, PENERAPAN GCG DI PERUSAHAAN YANG BERBASISKAN TEKNOLOGI INFORMASI UNTUK MEMPEROLEH KINERJA OPERASIONAL DAN KINERJA KEUANGAN YANG BERKUALITAS - Julisar Julisar (FEB Universitas Sultan Ageng Tirtayasa, 2016)
Due to increasing global competition, many enterprises are aware of the benefits of Enterprise Resource Planning. This study is focuses on aspects of the ERP utilized in manufacturing industries. This paper report on one suit case study application. The case was conducted by using interview and observation techniques. The Situation-Actor-Process (SAP) paradigm was used to analyze the case. A synthesis was performed in the management context, situational factors, processes used in ERP system and the relationship among the adherence to COSO, and GCG implementation. The resultant in learning issues in conjunction with the conclusion of the study may help in identifying the potential key areas in ERP implementation, adherence to COSO, and GCG implementation in accordance to get best quality in operational performance that has the implication to best quality to financial performance. Results reveal that top management support, mandate and commitment have positvely related to ERP implementation, adherence to COSO, and GCG implementation. Future research by using hypothesis development can be conducted to show whereas there are a positive relationship among the variables. Keywords: ERP Implementation, Adherence to COSO, GCG Implementation, Operational Performance, Financial Performance.